A circular economy approach for producing a fungal-based biopesticide employing pearl millet as a substrate and its economic evaluation. (December 2021) - Chaparro, Martha L.; Sanabria, Poldy J.; Jiménez, Ana M.; Gómez, Martha I.; Bautista, Eddy J.; Mesa, Leyanis
Abstract: This study aims to present a circular economy approach as regards developing a culture medium based on pearl millet as a substrate to produce Akanthomyces lecanii conidia for purposes of biopesticides employing solid-state fermentation (SSF) in polypropylene bags. The study was developed with two main focuses. First, on the evaluation of a culture medium based on pearl millet and a separation step. Second, a techno-economic analysis was carried out to evaluate the production costs of alternative processes. The best medium for biomass yield and enzymatic activities was the one with recycled pearl millet with 0.6% sugarcane molasses. The unitary production cost is reduced 32% when recycled pearl millet and sugarcane molasses are used as production mediums at highest production volume. These results show the economic advantages of introducing the concepts linked to a circular economy, such as recycle and recovery in biopesticide obtention from A. lecanii conidia.